Zeolite as a Feed Additive to Reduce Salmonella and Improve Production Performance in Broilers - Al-Nasser, Afaf Y.; Al-Zenki, Sameer F.; Al-Saffar, Abdulameer E.; Abdullah, Faten K.; Al-Bahouh, Mariam E.; Mashaly, Magdy (International Journal of Poultry Science, 2011)
Zeolite (clinopitolites) was added to broiler feed at concentrations of 1.0%, 1.5% or 2.0% and was evaluated for its effectiveness to reduce Salmonella in broilers and its effects on production performance. These experiments were conducted both in the summer and winter seasons. It was found that adding zeolite in the broiler diet significantly (p